2014
DOI: 10.14814/phy2.12218
|View full text |Cite
|
Sign up to set email alerts
|

Task complexity and maximal isometric strength gains through motor learning

Abstract: This study compared the effects of a simple versus complex contraction pattern on the acquisition, retention, and transfer of maximal isometric strength gains and reductions in force variability. A control group (N = 12) performed simple isometric contractions of the wrist flexors. An experimental group (N = 12) performed complex proprioceptive neuromuscular facilitation (PNF) contractions consisting of maximal isometric wrist extension immediately reversing force direction to wrist flexion within a single tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…However, most studies in this field examine the transfer of strength and skill separately following unique training paradigms (Keogh et al 2010;Ruddy and Carson 2013). Since all resistive exercise (i.e., strength training) includes a skill component, and therefore the potential for motor learning (Green et al 2014;McGuire et al 2014aMcGuire et al , 2014b, it is likely that a strengthtraining program results in the cross education of both strength and skill. Therefore, the present study investigated the presence of skill transfer (cross education of skill) following unilateral strength training.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies in this field examine the transfer of strength and skill separately following unique training paradigms (Keogh et al 2010;Ruddy and Carson 2013). Since all resistive exercise (i.e., strength training) includes a skill component, and therefore the potential for motor learning (Green et al 2014;McGuire et al 2014aMcGuire et al , 2014b, it is likely that a strengthtraining program results in the cross education of both strength and skill. Therefore, the present study investigated the presence of skill transfer (cross education of skill) following unilateral strength training.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced level of antagonist co-activation in the tibialis anterior muscle during plantarflexion suggested that, the functional improvements were partly due to motor learning. The level of co-activation is typically reduced at the early stages of strength training (18,22). The HIIT may thus have improved selective motor control, but it should be noted that reduction in the co-activation can occur also due to increased reciprocal inhibition at the spinal level (15).…”
Section: A C C E P T E D Discussionmentioning
confidence: 99%
“…Four of them dropped out due to personal reasons or illness. The remaining fourteen subjects (height 165 ± 5 cm, weight 67 ± 13 kg, age 22 ± 3, age range [16][17][18][19][20][21][22][23][24][25][26][27][28]1 under aged) participated in all tests and training sessions. The subjects were informed about the risks, requirements and benefits of the study before signing written consent.…”
Section: Subjectsmentioning
confidence: 99%